2005
DOI: 10.1163/1568537054068598
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Cognitive Science of New Religious Movements

Abstract: Traditionally cognitive scientists have had little to say about religion (and even less to say about new religious movements (NRMs)) partly because religion is arguably a social phenomenon (Bainbridge et al. 1994) and partly because of the pervasive scientific bias of relegating religion to the heap of the irrational, the illogical, and 'a fading vestige of the prescientific times' (Lewis 2003). While sociologists of religion have been studying NRMs, their analysis has been limited to the macro-level. Recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…For a diverse collection of sociological research using multi‐agent methods, see the January 2005 issue of the American Journal of Sociology (Gilbert and Abbott 2005). For recent working papers and on‐line articles that model religious beliefs or behavior using simulations and multi‐agent methods, see Chattoe (2005), Metzler (2002), Spickard (2005), and Upal (2005).…”
mentioning
confidence: 99%
“…For a diverse collection of sociological research using multi‐agent methods, see the January 2005 issue of the American Journal of Sociology (Gilbert and Abbott 2005). For recent working papers and on‐line articles that model religious beliefs or behavior using simulations and multi‐agent methods, see Chattoe (2005), Metzler (2002), Spickard (2005), and Upal (2005).…”
mentioning
confidence: 99%
“…While computational applications of religion still lack widespread use by scholars of religion, a number of pioneering studies have shown the poten tial advantage of this approach. These include studies of how socio-cultural and religious beliefs are created (Doran 1998;Hoffman 2002;Upal 2005a;2005b;Dow 2008), how cultural ideas spread in a population (Bainbridge 1995;Epstein 2001;Newman, Barabasi, and Watts 2006), studies of ritual behavior (Nielbo and Sorensen forthcoming; Kahn and Whitehouse 2010; Hochberg and Whitehouse 2010), and formation of the social structure of organizations (Prietula, Carley, and Gasser 1998). In the rest of this section we provide more detail of some of the studies that are most relevant to the scholars of religion.…”
Section: Applications In the Study Of Religionmentioning
confidence: 99%
“…Knowledge-rich Agent-based Social Simulation Upal (2005a;2005b;2007a; has argued that traditional agent-based social simulation systems assume representations that are too impoverished to result in the emergence of richly interconnected shared beliefs we call religious ideologies. Traditional agent-based social simulation systems are designed based on the keep-it-as-simple-as-possible principle.…”
Section: God From the Machinementioning
confidence: 99%
“…A series of recent studies (Packer 2007;Packer 2008) by the social psychologist Dominic Packer have found that high identifiers are indeed more likely to engage in norm-defying behavior if they believe that the group norms are harmful to the group's long term prosperity. Upal (2005c) focused on social identity beliefs which include, ''who belongs to the group and who does not, who is admitted to the group, and who is not? This is particularly clear for racist, ethnocentric, xenophobic or nationalist ideologies, according to which only 'we, white Europeans' belong in Europe, and others should not be admitted, at least not as (equal) citizens'' (van Dijk 1995) (Page 250).…”
Section: Social Identity Entrepreneurs (Ies) As Weavers Of Cultural Tmentioning
confidence: 99%